KUAT LENTUR BALOK TANPA TULANGAN DENGAN KEMIRINGAN SAMBUNGAN 45o DI ½ DAN ¼ BENTANG - Purnawirati, Neny (Universitas Bina Taruna Gorontalo, 2024)
This study aims to further investigate the effect of concrete beam joints on the flexural strength testing of beams with 1 loading point, beam fracture patterns due to the presence of joints where the concrete casting process in projects often cannot be completed in one series of castings.This can happen because the implementation method is applied in stages, the casting area is very large so the volume of concrete is very large and the limitations of manpower, equipment and materials. The result will be casting joints. What is being debated in the field is where the casting should be stopped. To answer this question, this research was conducted. The approach is carried out by testing the flexural strength of a concrete block measuring 15x20x120 cm. The compressive strength of the concrete used is f'c 20. This beam is without reinforcement. So the concrete behavior will be known without being affected by reinforcement. Casting of beams was carried out in 2 stages with 1 day casting time difference and the angle of inclination of the joints was 45o. Connections are made at ¼ and ½ beam span positions. As a form of reinforcement, concrete adhesive is added to the joints. Flexural strength testing was carried out at the age of 14, 21 and 28 days of concrete. The test results show that all beams that have joints are broken at the joints with a broken pattern according to the connection. Overall the beams that have flexural strength joints drop by up to 75%. Thus the casting process that is not complete will produce concrete joints that have the same risk and it cannot be determined which is better between joints in ¼ or ½ span. This proves that concrete joints are points that are prone to fracture due to bending.